2009
DOI: 10.3324/haematol.13486
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of assays designed for the quantification of JAK2V617F: a multicenter study

Abstract: The online version of this article contains a supplementary appendix. BackgroundMany different techniques have been designed for the quantification of JAK2V617F allelic burden, sometimes producing discrepant results. Design and MethodsJAK2V617F quantification techniques were compared among 16 centers using 11 assays based on quantitative polymerase chain reaction (with mutation-specific primers or probes, or fluorescent resonance energy transfer/melting curve analysis), allele-specific polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 27 publications
2
66
0
3
Order By: Relevance
“…A reduction of V617F allele burden consistent with the definition of 'partial response' according to the European LeukemiaNet (ELN) criteria [Barosi et al 2009] involved 15% of ET patients and 12% of PV patients. In summary, the bulk of current evidence seems to suggest that hydroxyurea can produce some reduction in the JAK2 V617F allele burden in subsets of patients [Girodon et al 2008;Ricksten et al 2008;Theocharides et al 2008], but the clinical relevance of this observation is questionable. On the other hand, it is clinically relevant that patients with PMF who harboured the JAK2 V617F mutation were more sensitive to hydroxyurea than the wild-type counterpart on multivariable analysis and that in PV the JAK2 V617F allele burden correlated directly with the response to drug and inversely with the daily dose in responding patients [Sirhan et al 2008].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction of V617F allele burden consistent with the definition of 'partial response' according to the European LeukemiaNet (ELN) criteria [Barosi et al 2009] involved 15% of ET patients and 12% of PV patients. In summary, the bulk of current evidence seems to suggest that hydroxyurea can produce some reduction in the JAK2 V617F allele burden in subsets of patients [Girodon et al 2008;Ricksten et al 2008;Theocharides et al 2008], but the clinical relevance of this observation is questionable. On the other hand, it is clinically relevant that patients with PMF who harboured the JAK2 V617F mutation were more sensitive to hydroxyurea than the wild-type counterpart on multivariable analysis and that in PV the JAK2 V617F allele burden correlated directly with the response to drug and inversely with the daily dose in responding patients [Sirhan et al 2008].…”
Section: Introductionmentioning
confidence: 99%
“…However, in five of six patients in whom hydroxyurea was started during the follow up, a statistically significant decrease of JAK2 V617F allele burden was reported after 6 months; halting the treatment caused the level of mutant allele to increase [Theocharides et al 2008]. Hussein and colleagues failed to observe changes in the V617F allele burden after hydroxyurea treatment [Hussein et al 2009], while Girodon and coworkers reported a significant reduction of mutant allele in 36 patients with PV or ET from a median of 43% at diagnosis to 24% at 15 months after starting hydroxyurea [Girodon et al 2008]. In three ET patients the mutation was no longer detectable after 555 months of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of JAK2WT and JAK2V617F Genomic DNA was prepared using QiaAmp DNA mini-kit (Qiagen, Valencia, CA, USA), and JAK2WT and JAK2V617F allele-specific quantitative PCRs were performed in genomic DNA and in cDNA as described (Lippert et al, 2006(Lippert et al, , 2009 Quantitative mRNA studies of cytokines and signalling molecules Cell pellets kept in Trizol were submitted to mRNA extraction. After DNAse treatment and reverse transcription, cDNAs were kept frozen at À80 1C.…”
Section: Patientsmentioning
confidence: 99%
“…31 Here we present a prognostic model that is based on a relatively large cohort. The internal validation of this model was confirmed by bootstrap resampling.…”
Section: Tive Pcr Although the Jak2mentioning
confidence: 99%